Education strategy in the developing world revising the World Bank's education policy - Collins, Christopher S.; Wiseman, Alexander W. 1968- (Emerald, 2012)
Following the development of a "Concept Note" for the World Bank Education Strategy 2020, the World Bank engaged in a series of activities to garner feedback about the new strategy. In early 2011, a revised strategy was published entitled, "Learning for All: Investing in People's Knowledge and Skills to Promote Development." The document ranges from explaining the role of education in development to the philosophy behind a new strategy and concludes with details about performance and impact indicators. To bring together the scholarly work and both evidence and expert opinion about the development practices of the Bank, this volume includes chapters/authors with a range of research interests, practical experience, and ideological backgrounds.
Includes indexes.
Keywords: World Bank.